The Beta‑Convergence of the EU–10 Countries and Regions in the Years 2004–2015 - Wołkonowski, Jarosław (Comparative Economic Research. Central and Eastern Europe, 2019)
The article analyzes the beta‑convergence of the EU–10 countries and the EU–15 for 2004 and 2015 at four levels – the state, NUTS 1, NUTS 2 and NUTS 3. The strongest beta‑convergence is at the level of the EU–10 countries; however, the lower the level of the regional unit, the weaker the beta‑convergence. At the NUTS 3 level in Poland, Slovenia and Hungary, divergence was found, which means there are convergence and divergence processes.